(untitled) (Mediscope, 2016)
Pregnancy induced hypertension (PIH) complicates approximately 6% of pregnancies globally and it is the most important cause of maternal and neonatal morbidity and mortality. The purpose of the cross sectional descriptive type of study was to assess the socio-demographic/economic characteristics of women with PIH in a selected tertiary care hospital. Respondents were selected by purposive sampling technique and data were collected by face to face interview using a semistructured type of questionnaire. In this study, the number purposively selected respondents was 113 who came for treatment in gynecology and obstetrics related inpatient and outpatient departments of the hospital. It was found that the age of mothers was directly and significantly (p < 0.01) associated with PIH. The development of PIH was higher in the educated mothers than illiterate or less educated mothers. The relationship between PIH and educational status was significant (p < 0.01). The association between the proportion of mothers with PIH and family history of hypertension was also statistically significant (p < 0.01). Awareness regarding the associated risk factors for PIH shall be helpful in reducing the PIH related morbidity and mortality. Mediscope Vol. 3, No. 2: July 2016, Pages 31-35